Surveillance Instructions and Knowledge Among African American Colorectal Cancer Survivors - Pisu, Maria (American Society of Clinical Oncology, 2014)
INTRODUCTION: African Americans are less likely than other racial/ethnic groups to receive appropriate surveillance, an important component of care to achieve better long-term outcomes and well-being after colorectal cancer (CRC) treatment. This study explored survivors' understanding of surveillance instructions and purpose. PATIENTS AND METHODS: Interviews with 60 African American CRC survivors were recorded and transcribed. Compliance with surveillance guidelines was defined by disease stage and self-reported tests. Four coders (blind to compliance status) independently reviewed transcripts. Frequency of themes was reported by compliance status. RESULTS: Survivors (4 to 6 years postdiagnosis; women, 57%; age ≥ 65 years, 60%; rural location, 57%; early-stage disease, 62%) were 48% noncompliant. Most survivors reported receiving surveillance instructions from providers (compliant, 80%; noncompliant, 76%). There was variation in recommended frequency of procedures (eg, every 3 or 12 months) and in importance of surveillance stressed by physicians. Most survivors understood the need for follow-up (compliant, 87%; noncompliant, 79%). Lack of knowledge of/interest in surveillance was more common among noncompliant individuals (compliant, 32%; noncompliant, 52%). CONCLUSION: Patients' limited understanding about the importance of CRC surveillance and procedures may negatively affect compliance with recommendations in African American CRC survivors. Clear and enhanced communications about post-treatment recommendations in this population are warranted.